Luwian hieroglyphic texts in late Bronze Age scribal tradition - Woudhuizen, Fred (Dresdner Beiträge zur Hethitologie, 2021)
Cover -- Title Pages -- Contents -- Introduction -- List of Abbreviations -- Chart I. Synchronisms between the royal houses of Khatti, Karkamis, and Assuwa/Arzawa/Mira -- PART I: THE TEXTS -- 1. THE LEGEND OF SEAL BOROWSKI NO. 26 -- 2. THE ANKARA SILVER BOWL (ANKARA 2) -- 3. THE ANKARA BRONZE BOWL (ANKARA 3) -- 4. DEDICATION OF TEMPLES BY TALMISARRUMAS OF ALEPPO -- 5. THE VICTORY STELE OF TUHKANTI URKHITESUP -- 6. THE ROCK RELIEF OF TAŞÇI -- 7. A BOWL AND ALTAR DEDICATED BY THE SCRIBE TAPRAMIS -- 8. THE LYCIAN CAMPAIGN OF TUDKHALIYAS IV -- 9. OFFERING REGULATIONS ON THE EMİRGAZİ STONE ALTARS -- 10. THE STONE INSCRIPTION FROM KARAKUYU -- 11. SAUSKARUNTIAS' CAPTURE OF ATTARIMA -- 12. PUDUKHEPA'S MEMORIAL AT FRAKTİN -- 13. SUPPILULIUMAS II'S PIETAS TOWARDS HIS FATHER -- 14. THE DEEDS OF SUPPILULIUMAS II FOR ONE YEAR -- EXCURSUS ON THE DATE OF THE SÜDBURG TEXT: SUPPILULIUMAS I OR II? -- (1) Tarkhuntassa -- (2-3) Wiyanawanda and Lukka -- 15. THE STELE FROM AFYON -- 16. THE ORTHOSTAT FROM TORBALI -- 17. THE ROCK INSCRIPTION OF LATMOS (SURATKAYA) -- 18. THE STELE OF ANAZITIS FROM ÇALAPVERDİ -- 19. THE SPRING PRECINCT AT BOĞAZKÖY ERECTED BY A KING OF ISUWA -- 20. GREAT KING KUPANTAKURUNTAS III OF MIRA, MUKSUS, AND THE SEA PEOPLES EVENT -- 20.1 INTRODUCTION -- 20.2 THE LUWIAN HIEROGLYPHIC TEXT FROM BEYKÖY -- 20.3 SIGNIFICANCE OF BEYKÖY 2 -- 20.4 ARGUMENTS FOR AND AGAINST AUTHENTICITY -- EXCURSUS: ARGUMENTS FOR THE AUTHENTICITY OF BEYKÖY 2 -- 1. INTRODUCTION -- 2. MATERIAL IN MELLAART'S ESTATE -- 3. THE RESEARCH HISTORY -- 4. THE SEQUENCE OF THE BLOCKS -- 5. THE DATE OF THE DRAWING -- 6. LINGUISTIC ANALYSIS -- 7. COMPARING BEYKÖY 2 WITH THE SEA PEOPLES INSCRIPTIONS IN MEDINET HABU -- 8. CONCLUSIONS -- 21. MUKSAS' REALM IN THE TROAD -- 22. WALWAMUWAS' REALM OF SEKHA -- 23. SEKHA'S SEKUNDOGENITUR -- 24. THE RECOVERY PROGRAM OF GREAT KING ARITESUP OF KHATTI.